Evaluation of Patient Identification in Laras Hati Clinic - Tria Harsiwi Nurul Insani (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2021)
The aim of this research was to evaluate the implementation of patient identification in Laras Hati Clinic. The type of research used in this study is descriptive with qualitative approach. The subject of this study consist of nurse and midwife in Laras Hati Clinic. This research has been carried out since August 2018 until October 2018. The Implementation of identification patient in Laras Hati Clinic has not implemented optimally. patient identification wristbands are not completely available. There were no operational procedure in the use of wristbands and procedures for implementing patient identification. It has been implemented but the implementation has not been optimal. It caused by the unavailability of policies and standard operational procedures in the implementation of patient identification and identification patient wristbands, and also the patient safety culture has not yet been established in this clinic.Keyword : Evaluation, Patient Identification